Del trabajo mercantil individual hacia el trabajo asociativo autogestionario. Análisis de la cooperativa de servicios de construcción Cuenca - Segarra Ortega, Yessenia Elizabeth (2023)
The construction sector is one of those that contributes to boost the economy, however it is characterized by job insecurity that is caused by temporary contracts that are made to comply with a construction project. For this reason, the labor supply is characterized by having low levels of schooling that generates low-skilled labor that is employed in the informal sector; They make individual commercial work an inconvenience to generate income to cover the need. Hence, self managed associative work emerges as an opportunity, but given the prevalence of capitalist thought, the transition towards the philosophy that seeks collective well-being is limited. In this sense, the objective of this research is to analyze the transition process from individual mercantile work to self managed associative work of the Cuenca Construction Services Cooperative, which has been operating since 2018. To achieve what was proposed, qualitative research was used. through the ethnographic method with the application of techniques such as participant observation and semi structured interviews. The results show that the factors that motivated the sector of workers to join the associative work are the lack of employment and job insecurity. While the transition process presents difficulties by involving a change of mentality in the partners and in aspects of improvement, the error of associating individuals who do not have entrepreneurial experience stands out, as well as the lack of contribution of own capital that facilitates the termination of the cooperative.